Feminist theory today : an introduction to second-wave feminism - Evans, Judith (Sage Publications, 1995)
This stimulating text presents a concise and accessible introduction to feminist theory today. Covering all the major variants of feminist political thought, it offers a unique examination of the archive of modern feminist theory from the publication of The Feminine Mystique in 1963 to current postmodernist and legal feminist texts. It provides both an intellectual history and a political critique of contemporary feminism in the United States and in the United Kingdom. Judith Evans focuses on the divergence within, as well as between, feminist schools, and on protests from women marginalized by `the movement' - including those who are lesbian and those who are black.